Ab initio studies of coherent spin transport in Fe-hBN/graphene van der Waals multilayers. (9th June 2017) - Ukpong, Aniekan Magnus
Abstract: This paper presents the results of ab initio studies of the electronic spin inversion and filtering in a ferromagnetic multilayer heterostructure. Spin-polarized electronic structure calculations are performed based on van der Waals density functional theory to give unique insights in to the generation, manipulation and transport of coherent spin conductance. By using an exact theory of the self-consistent ground state of the Fe-hBN/graphene multilayer as a model of the magnetic tunnel junction, hidden asymmetries are unraveled in the spin-resolved charge densities. It is shown that the injection of spin into the graphene/boron nitride tunnel layer from a ferromagnetic contact gives rise to coherent spin current. The projected Fermi surfaces of the up and down spin channels are analyzed to reveal Fermi arc topologies and spin anisotropies. It is also demonstrated that the coherent transport of pure spin-down current in the topological Weyl semimetal phase is robust. The implications of the results on out-of-plane transport of spin polarized conductance in van der Waals multilayer spintronic devices is discussed. The insights derived from this study are expected to open up prospects for further exploration of van der Waals magnetic multilayer heterostructures as a versatile platform for developing materials for Weyltronic applications.